THE DEVELOPMENT OF TOURISM AS ONE OF THE PROMISING DIRECTIONS OF OVERCOMING MACROECONOMIC CHALLENGES THE COUNTRIES IN THE CONDITIONS OF TRANSFORMATION OF SOCIETY - Шупик, І. І. (Scientific Progress & Innovations, 2014)
Proved the importance of the tourism industry as one of the promising directions of solving a wide range of macroeconomic problems in the period of transformation of society, which will allow stabilizujace socio - economic situation in the country and to improve the quality characteristics of living. Defined major directions of the impact of tourism activities on socio-economic development of the country and the reasons for their cause. Emphasized that the achievement of goals is possible only if a consistent and responsible actions of the government, its constant interaction with the public, business.